Studi Aktivitas Pemasaran Film Independen: Kasus di Indonesia - Achmad Eriansyah Utama Putra; Agnes Juliarti; Dimas Mohammad Wibowo; Figra Ardham; Vera Julianti (Universitas Prasetiya Mulya, 2019)
The independent film industry in Indonesia is both interesting and unique sector because it has different characteristics from the commercial film industry. The study was conducted to identify independent film marketing activities through a marketing mix and the factors that can influence the marketing activities of independent films in Indonesia. This is a qualitative research using in-depth interview as the main method. Interviews were conducted to nine participants in the film industry representing three chains of production, distribution and exhibition that forms the synergies in the film industry. The main research finding is eight factors influenced independent film marketing activities: idealism, story line, expressions, aspirations, actualization, film distribution channels, promotional activities, and regulation.